ECOTOURISM DEVELOPMENT STRATEGY OF AEK MARTUAWATERFALL IN ROKAN HULU DISTRICT, RIAU PROVINCE - Mulya Rolina; Defri Yoza; Nurul Qomar (Jurusan Kehutanan Fakultas Pertanian Universitas Riau, 2020)
Rokan Hulu District is a district has own attractiveness which is in natural beauty in the form of waterfall, one of which is the Aek Martua waterfall located in the Bangun Purba Village. The purpose of this study as to find out the potential of tourism objects in order to improve the development of Aek Martua waterfall ecoutourism and to develop a strategy for developing Aek Martua waterfall ecoutourism in Rokan Hulu District. This study use interview methods and field observation. The status of the Aek Martua waterfall area is a Nature Reserve or Nature Conservation Area. The result of the study show that the waterfall has its own potential, which is a different height, there are three waterfall with a distance of several tens of meters starting from a height of 15 to 35 meters. Aek Martua waterfall ecotourism development strategy can be carried out such as developing Aek Martua waterfall as a location for ecotourism in ancient wake village, building facilities and infrastructure, improving road access to the location of Aek Martua waterfall, empowering communities around Aek Martua waterfall in ecotourism activities, increasing collaboration its local government to develop Aek Martua waterfall ecotourism, increased security from illegal logging that occurs around the Aek Martua waterfall area, and promoting waterfall ecotourism through internet, television, and newspaper.